NFIL3 Suppresses Hypoxia‐induced Apoptotic Cell Death by Targeting the Insulin‐like Growth Factor 2 Receptor. Issue 6 (10th April 2015) - Lin, Kuan‐Ho; Kuo, Chia‐Hua; Kuo, Wei‐Wen; Ho, Tsung‐Jung; Pai, Peiying; Chen, Wei‐Kung; Pan, Lung‐Fa; Wang, Chien‐Cheng; Padma, V. Vijaya; Huang, Chih‐Yang
ABSTRACT: The insulin‐like growth factor‐II/mannose 6‐phosphate receptor (IGF2R) over‐expression correlates with heart disease progression. The IGF2R is not only an IGF2 clearance receptor, but it also triggers signal transduction, resulting in cardiac hypertrophy, apoptosis and fibrosis. The present study investigated the nuclear factor IL‐3 (NFIL3), a transcription factor of the basic leucine zipper superfamily, and its potential pro‐survival effects in cardiomyocytes. NFIL3 might play a key role in heart development and act as a survival factor in the heart, but the regulatory mechanisms are still unclear. IGF2 and IGF2R protein expression were highly increased in rat hearts subjected to hemorrhagic shock. IGF2R protein expression was also up‐regulated in H9c2 cells exposed to hypoxia. Over‐expression of NFIL3 in H9c2 cardiomyoblast cells inhibited the induction of hypoxia‐induced apoptosis and down‐regulated IGF2R expression levels. Gel shift assay, double‐stranded DNA pull‐down assay and chromatin immune‐precipitation analyses indicated that NFIL3 binds directly to the IGF2R promoter region. Using a luciferase assay, we further observed NFIL3 repress IGF2R gene promoter activity. Our results demonstrate that NFIL3 is an important negative transcription factor, which through binding to the promoter of IGF2R, suppresses the apoptosis induced by IGF2R signaling in H9c2 cardiomyoblast cells under hypoxic conditions. J. Cell. Biochem. 116: 1113–1120, 2015. © 2015 Wiley Periodicals, Inc.